EVALUASI PENERIMAAN JEJARING SOSIAL GOOGLE+ PADA SISWA SEKOLAH MENENGAH ATAS DI WILAYAH JAKARTA SELATAN - Abdul Mufti; Fitriana Destiawati; Tri Yani Akhirina (Jurnal Sistem Informasi, 2014)
Based on the research in the first year high school students in Jakarta Google+ social networking technologies application is ready and accept the Google+ social networking technology but not to the use of a continuous basis. Therefore there is need for the development of the research is to use the model Unified Theory Of Acceptance And Use Of Technology (UTAUT). This study was conducted to evaluate the acceptance of the Google+ social network that has been done in the first phase of the study. Based on the results of the first phase of the research is still considered less acceptable social networking Google + as a learning medium high school students. The present study is expected to implement Google+ as a social network that can be used to accomplish more tasks. The method used for processing the data is to use the analysis technique of Structural Equation Model (SEM). The results of this study is the use of Google technology among high school students is strongly influenced by the condition of the supporting facilities for both girls and boys. If the environmental conditions and good supporting facilities, the interest of high school students to use technology Google+ will be even greater